أحكام الدخول في قانون الأسرة - سعيد، محمودي (جامعة أحمد دراية أدرار, 2023)
الزواج عقد رضائي يتم بين رجل وامرأة شرعا وقانونا من أجل تحقيق مجموعة من الغايات الاجتماعية والإنسانية. لا يحقق هدفه بمجرد العقد، وإنما يجب أن يتم الدخول بالزوجة، الذي تترتب عنه مجموعة من الآثار تقع على هذا العقد. هذه الآثار تمس، بالدرجة الأولى، الصداق لأنه حق للزوجة، تتبعه النفقة الغذائية وما يلحقها من كسوة ومسكن وعلاج. فالدخول بالزوجة يجعلها تخدم مصالحه. وبالدخول أيضا يتحقق الاتصال الجنسي المشروع التي ينتج عنه أولاد شرعيون يلحقون أباهم في النسب. ومتى لم يتحقق الدخول فإن الولد لا ينسب لأبيه عملا بنص المادة 40 من قانون الأسرة الجزائري. Marriage is a consensual contract between a man and a woman according to Islamic law in order to achieve a set of social and humanitarian goals. He does not achieve his goal just by doing the contract, but the consummation of the marriage must take place. Because the entry entails a set of effects on the marriage contract. These effects affect, in the first place, the dowry because it is the right of the wife, followed by the food maintenance and the clothing, housing and treatment that follows her. Because consummation with the wife makes her serve his interests. By entering also, legal sexual intercourse is achieved, which results in legitimate children who follow their father in lineage. The child is not attributed to his father, pursuant to Article 40 of the Algerian Family Code.
Keywords: قانون الأسرة -- الفقه الإسلامي -- النفقة الزوجية -- الجزائر